Asociaţia Farmaciilor veterinare, istoric în context European - Andrei Răutu (Medicamentul Veterinar)
In this PPT, a presentation is made in the European context of the Association of Romanian Veterinary Pharmacies. Thus, it is presented that the following are currently registered in the Association: companies with veterinary pharmacies: 130/1421, representing 9%, independent pharmacies: 397/1890, representing 21%, which represents in all counties of Romania, between 9.1% (in Iasi County) and respectively 57.9% (in Brăila county). The evolution of members was from 30 active in 2020, to 130 in 2023. Compared to 2020, members from 31 counties out of a total of 41 signed up. The regulatory restrictions in the European area related to the activity of sale of veterinary medicine and the involvement of the doctor/veterinarian in the sale.